Impact of health insurance in the economics of Peruvian households, 2010-2019 - Zavala-Curzo, David Fernando (2023)
Objective: To determine the impact of health insurance in the economy of Peruvian households during the 2010-2019 period. Material and Methods: This is a cross-sectional analytical study that used the database of the National Peruvian Household Surveys from years 2010, 2014, and 2019, aiming to analyze the impact of health insurance in terms of pocket money spending for health issues, catastrophic healthcare spending, and impoverishment in Peruvian households, and also to determine the presence of other associated factors. Results: During the study period, it was observed that Peruvian households reduced their monthly average pocket money spending for health issues (119.9 PEN in 2010 and 107.9 PEN in 2029), as well as the percentage of household with catastrophic healthcare expenses (4.06% in 2010 to 3.47% in 2019), and the percentage of households who became impoverished because of pocket money expenses for health issues (1.78% in 2020 to 1.51% in 2019). Factors associated to catastrophic healthcare expenses and to impoverishment were lower educational level for the household leader, the presence of family members with chronic diseases, and living in a rural area. The absence of health insurance was significantly associated to a greater risk for catastrophic healthcare expenses, but not to impoverishment. Conclusions: Increased healthcare insurance coverage contributes to financial protection of Peruvian households against pocket money spending for health issues; however, barriers for effective access to healthcare services, and other socioeconomical factors may significantly limit this impact.